2015
DOI: 10.1002/acn3.223
|View full text |Cite
|
Sign up to set email alerts
|

F‐box/ LRR ‐repeat protein 7 is genetically associated with Alzheimer's disease

Abstract: ObjectiveIn the context of late-onset Alzheimer’s disease (LOAD) over 20 genes have been identified but, aside APOE, all show small effect sizes, leaving a large part of the genetic component unexplained. Admixed populations, such as Caribbean Hispanics, can provide a valuable contribution because of their unique genetic profile and higher incidence of the disease. We aimed to identify novel loci associated with LOAD.MethodsAbout 4514 unrelated Caribbean Hispanics (2451 cases and 2063 controls) were selected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 42 publications
4
44
0
Order By: Relevance
“…While the exact role of FBXL7 is still unknown, F-box proteins, of which FBXL7 is a member, are thought to be involved in cell growth, survival, and cell death [38]. This study along with a report by Lee et al also confirmed several risk loci as nominally significant in non-Hispanic Whites: CLU , PICALM , BIN1 , CD33 , FERMT2 , CELF1 , SLC24A4-RIN3 , and ABCA7 [15••, 33]. Further, in a GWAS of African Americans, ABCA7 was found to be genome-wide significant, and CR1 , BIN1 , EPHA1 , and CD33 [37••, 39] were replicated as well.…”
Section: Gwasmentioning
confidence: 54%
See 2 more Smart Citations
“…While the exact role of FBXL7 is still unknown, F-box proteins, of which FBXL7 is a member, are thought to be involved in cell growth, survival, and cell death [38]. This study along with a report by Lee et al also confirmed several risk loci as nominally significant in non-Hispanic Whites: CLU , PICALM , BIN1 , CD33 , FERMT2 , CELF1 , SLC24A4-RIN3 , and ABCA7 [15••, 33]. Further, in a GWAS of African Americans, ABCA7 was found to be genome-wide significant, and CR1 , BIN1 , EPHA1 , and CD33 [37••, 39] were replicated as well.…”
Section: Gwasmentioning
confidence: 54%
“…In a study of persons of Caribbean Hispanic descent, a novel locus on chromosome 5, FBXL7 , met genome-wide significance [15••]. While the exact role of FBXL7 is still unknown, F-box proteins, of which FBXL7 is a member, are thought to be involved in cell growth, survival, and cell death [38].…”
Section: Gwasmentioning
confidence: 99%
See 1 more Smart Citation
“…; 2,451 cases and 2,063 controls) [41] . Second, the re-analysis of IGAP data after stratification on the APOE genotype unraveled a locus located near the MAPT gene which encodes the Tau protein [42] , which still remains to be replicated in independent studies.…”
Section: Results From Gwasmentioning
confidence: 99%
“…The study has been described in detail elsewhere. 16 Collection of data for the WHICAP has been ongoing since 1992; these data were used as a replication sample for the present study. The WHICAP was approved by the institutional review board of Columbia University, New York City, and all participants provided written informed consent.…”
Section: Methodsmentioning
confidence: 99%